2020
DOI: 10.1111/joor.13072
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory function and oral health‐related quality of life of patients with atrophic and non‐atrophic mandibles using implant‐retained mandibular overdentures: 3‐year results of a prospective clinical study

Abstract: Background Long‐term changes in masticatory function, oral health‐related quality of life (OHRQoL) and prosthetic complications in implant‐retained mandibular overdenture (IMO) wearers as a function of bone atrophy require detailed investigations. Objective Investigating the evolution of masticatory function, OHRQoL and prosthetic occurrences of IMO wearers according to mandibular bone atrophy over 3 years of usage. Methods This study evaluated 26 IMO wearers after 2 and 3 years of IMO loading categorised acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Sligthly lower subjective satisfaction of patients were found in a retrospective study from Germany with 37 hypodontia patients recruited 0.5-16 years after implantation, however the results were then improved by using objective assessments [33]. Despite of the small sample size of patients with implant-supported removable prostheses in our study (only five patients), a great OHRQoL among the patients with implant-supported removable prostheses could also be confirmed, even though none of the removable prostheses were free from clinical complications and require more prosthetic maintenance [34].…”
Section: Patient Satisfactionmentioning
confidence: 64%
“…Sligthly lower subjective satisfaction of patients were found in a retrospective study from Germany with 37 hypodontia patients recruited 0.5-16 years after implantation, however the results were then improved by using objective assessments [33]. Despite of the small sample size of patients with implant-supported removable prostheses in our study (only five patients), a great OHRQoL among the patients with implant-supported removable prostheses could also be confirmed, even though none of the removable prostheses were free from clinical complications and require more prosthetic maintenance [34].…”
Section: Patient Satisfactionmentioning
confidence: 64%
“…The question arises as to whether bone atrophy has an impact on the oral health‐related quality of life of patients treated with implant‐retained overdentures, foremost in the mandibular region. A 3‐year prospective study compared patients treated with implant‐retained mandibular overdentures with and without atrophic mandibles and, interestingly, did not reveal any statistical significant differences 56 . More recent studies support the finding that retention and therefore better stability of prostheses appears to be an important factor for patients’ oral health‐related quality of life 57,58 .…”
Section: Resultsmentioning
confidence: 93%
“…Those results might be related to the prosthesis design (reinforcement, resin thickness), implant number or position, and degree of residual ridge resorption. 2,3,6 In the event of overdenture fracture, the use of a thin layer of acrylic resin surrounding the metal housing of standard implants can result in stress concentration, crack formation, and ultimately prosthesis fracture. 4 Because the components associated with mini-implants are smaller, a thicker resin layer would be present around them, and consequently fracture may be mitigated.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, the change of retention inserts was reported to be the most frequent prosthetic maintenance in patients with IODs. 2,5,22,25,26 These results might be related to the implant design, but mostly to the load distribution in the prosthesis, in which the occlusion forces might not only be concentrated in the nylon component. Consequently, because IODs retained by mini-implants have a large mucosal support area, this structure can act as a stress-breaking element, explaining the fewer changes of retention inserts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation